The exchange of health and performance information when transitioning from club to National football teams: A Delphi survey of National team practitioners. Issue 6 (June 2022) - McCall, Alan; Davison, Mike; Massey, Andrew; Oester, Chelsea; Weber, Alexis; Buckthorpe, Matthew; Duffield, Rob
Abstract: Objectives: To establish agreement in National team contexts when players transition from club to National team about (i) what medical and physical information to collect, (ii) how to use information (iii) identifying challenges to collection and (iv) collection methods. Design: Delphi survey. Methods: A series of sequential online questionnaires were sent to heads of medical and performance of the 32 National teams following the FIFA 2018 World Cup. Two separate Delphi's; 'Medical' and 'Physical' were administered. The 'Medical' respondent was the person responsible for player health. 'Physical' referred to the person responsible for physical performance. Content analyses were performed, with subsequent rounds designed according to responses of the previous. Agreement was considered at ≥70%. Results: Twenty-three Medical (72%) and 14 (44%) Physical heads participated in Round 1 (3 rounds total). Seventeen Medical and 12 Physical respondents completed all rounds. Medical information agreed upon injury epidemiology, screening and injury treatment strategies. Physical information included training/match-loads, fatigue, wellness and current exercise programmes. Both Medical and Physical agreed information should be used to plan and individualise player programmes. Additionally medical information should guide coaches' national team selection. Communication, willingness to share and quality/completeness of information were agreed as main challenges. Medical and Physical respondents agreed a standardised reporting form and electronic shared database as best option to collect information. Conclusions: Our findings highlight the importance of health and performance information exchange between national and club teams. Further, this exchange should be cooperative, symbiotic and a two-way process to assist with improving player health.